Acute topics in anti-doping - Rabin, Olivier; Pitsiladis, Yannis 1967- (Medicine and sport science / series editors Dennis J. Caine, Andrew P. Hills, Timothy Noakes, 2017)
Doping represents the dark side of amateur and professional sports - in order to protect athletes around the globe, anti-doping rules are continuously revised and improved. This publication reviews the current regulatory framework, scientific aspects, future approaches, and social and ethical dimensions of the fight against doping in sport. Prominent experts on the implementation of anti-doping strategies, as well as leading researchers in science and medicine, have contributed to this publication. In keeping with its interdisciplinary origin, the book is intended for athletes, coaches, students, scientists, anti-doping officials, and all others interested in anti-doping and sports. Ranging from legal and educational to scientific and medical issues, this collection emphasizes the need for a multidisciplinary approach and the importance of preventative strategies in the fight against doping in sports.